2013
DOI: 10.1002/chem.201300588
|View full text |Cite
|
Sign up to set email alerts
|

Aptamer‐Based Turn‐On Detection of Thrombin in Biological Fluids Based on Efficient Phosphorescence Energy Transfer from Mn‐Doped ZnS Quantum Dots to Carbon Nanodots

Abstract: This paper presents the first example of a sensitive, selective, and stable phosphorescent sensor based on phosphorescence energy transfer (PET) for thrombin that functions through thrombin-aptamer recognition events. In this work, an efficient PET donor-acceptor pair using Mn-doped ZnS quantum dots labeled with thrombin-binding aptamers (TBA QDs) as donors, and carbon nanodots (CNDs) as acceptors has been constructed. Due to the π-π stacking interaction between aptamer and CNDs, the energy donor and acceptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 105 publications
0
40
0
Order By: Relevance
“…‘Activatable’ probes can be superior to ‘always on’ probes since they emit much less fluorescence in the absence of a target, thereby increasing the signal-to-background ratio (26,27). Our experiments with fluorescence spectroscopy revealed that AAFP emitted minimal fluorescence in the absence of HepG2 cells, likely reflecting fluorescence resonance energy transfer between the fluorophore and quencher lying close together in the hairpin structure formed upon hybridization of the two C-strands.…”
Section: Discussionmentioning
confidence: 99%
“…‘Activatable’ probes can be superior to ‘always on’ probes since they emit much less fluorescence in the absence of a target, thereby increasing the signal-to-background ratio (26,27). Our experiments with fluorescence spectroscopy revealed that AAFP emitted minimal fluorescence in the absence of HepG2 cells, likely reflecting fluorescence resonance energy transfer between the fluorophore and quencher lying close together in the hairpin structure formed upon hybridization of the two C-strands.…”
Section: Discussionmentioning
confidence: 99%
“…Its optical sensing is based on the interaction of a fraction of atoms/molecules on a treated surface, which strongly affects the recombination of electrons and holes within the particles, and in turn the emission response . Following this process, many analytes have been successfully detected, such as ions (Hg 2 þ , Co 2 þ , Zn 2 þ and Zr 4 þ ) (Bian et al, 2014;Gong et al, 2014a;Ren et al, 2011;Tan et al, 2012); proteins/enzymes, clenbuterol and glucose in biological fluids (Gong et al, 2014b;Wu et al, 2013;Wu et al, 2010;Zhang et al, 2013); organophosphorus pesticides (Ban et al, 2014); phenols in different media (Liu et al, 2010;Wei et al, 2015;Zhang et al, 2015b); and cathecol, domoic acid, rutin, urea, idarubicin and DNA (Bi et al, 2014;Dan et al, 2013;Ertas et al, 2015;Miao et al, 2014;Wang et al, 2013). Recently, Bian and co-workers, employing N-acetyl-L-cysteine and L-cysteine capped ZnS:Mn QDs as probes, showed the luminescent detection of L-ascorbic acid (AA) with high selectivity and long luminescence lifetime (Bian et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, another aptamer-based turn-on thrombin biosensor was based on Mn-doped ZnS quantum dots, whose phosphorescence was restored after thrombin-aptamer recognition [176]. The system involved an efficient phosphorescence energy transfer (PET) donoracceptor pair: Mn-doped ZnS quantum dots labeled with thrombinbinding aptamers (TBA QDs) as donors, and carbon nanodots (CNDs) as acceptors.…”
Section: Thrombin Detection By Tba and Its Variants: A Biologically Rmentioning
confidence: 99%